2022
DOI: 10.3389/fneur.2022.956208
|View full text |Cite
|
Sign up to set email alerts
|

Associations of sleep apnea risk and oxygen desaturation indices with cerebral small vessel disease burden in patients with stroke

Abstract: BackgroundObstructive sleep apnea (OSA) is associated with cerebral small vessel disease (CSVD). Nonetheless, whether OSA-risk determined by a simple screening questionnaire or indices quantifying nocturnal hypoxemia other than the conventional apnea–hypopnea index (AHI) by the home sleep apnea test (HSAT) associated with CSVD burden remains uncertain.MethodsFrom 2018 to 2021, we recruited patients with transient ischemic attack (TIA)/minor stroke from the Queen Mary Hospital Acute Stroke Unit and TIA/Stroke O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The relationship between OSA and cerebral infarction remains controversial. Studies have suggested that OSA can lead to an adverse prognosis in cerebral infarction, impair brain function, exacerbate cognitive dysfunction, and increase mortality risk (30)(31)(32)(33). The main mechanisms underlying these adverse outcomes include chronic intermittent hypoxia, sympathetic activation, changes in cerebral blood flow, oxidative stress, systemic inflammation, hypercoagulability, and endothelial dysfunction (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between OSA and cerebral infarction remains controversial. Studies have suggested that OSA can lead to an adverse prognosis in cerebral infarction, impair brain function, exacerbate cognitive dysfunction, and increase mortality risk (30)(31)(32)(33). The main mechanisms underlying these adverse outcomes include chronic intermittent hypoxia, sympathetic activation, changes in cerebral blood flow, oxidative stress, systemic inflammation, hypercoagulability, and endothelial dysfunction (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in addition to identifying several known risk factors, multivariate logistic regression and SHAP analysis also found that CT90/10, a variable that had been overlooked in previous cardiovascular studies, also plays an important role in OSA-related hypertension. Previous studies have shown a significant association between CT90 and Coronary Artery Calcium, cerebral small vessel disease and diabetic nephropathy ( 30 32 ), but the relationship between CT90 and hypertension has not been explored. The underlying causes by OSA and hypertension have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%